The effects of water stress and recovery periods on soluble sugars and starch content in cucumber cultivars - (:unkn) unknown (My University, 2010)
Changes in growth and carbohydrate content have been investigated in leaves of two cucumber cultivars from Turkiye, Beit Alpha 434 (B. 434) and Cengelkoy (C.M.C), under water stress and during subsequent recovery periods, following the restoration of normal water supply. Significant differences were found between these cultivars in their growth responses to and tolerance of stress treatments and in their carbohydrate metabolism. Soluble sugars and starch contents, detected under moderate (MS) and severe (SS) stress by enzymic methods, were compared with values from unstressed control plants (C). Hexoses were the major sugars in unstressed levels but no significant differences were detected in the amounts of individual hexoses from Control, MS and SS conditions. Sucrose (SU) contents were surprisingly low, even in unstressed levels and showed little change with stress, whereas the substantial amounts of starch in leaves of both cultivars, decreased rapidly with increasing stress. Two days after rewatering (2d), glucose (G) was the major sugar and appeared to increase slightly in previously stressed plants but, four days (4d) after return to normal watering, still remained significantly lower than in control plants of B. 434. The metabolic interpretation of there observations is discussed. © by PSP.
Keywords: Cucumber; Starch; Sugars; Water stress